Seed Availability Within Food Plots and Native Vegetation Areas on a Longleaf Pine Site in Southeastern Louisiana - Michael W. Olinde (National Quail Symposium Proceedings, 2017)
The lack of late winter foods has been hypothesized as a limiting factor for northern bobwhites in Louisiana pinelands. We determined January seed availability within food plots (rectangular and strip) and native vegetation areas on a longleaf pine site. Planted sites had considerably more seed available than native vegetation sites. However, most seeds were those of native grasses and sedges and not agricultural crops.